Protecting collective rights in Colombia - Laura Cecilia Gamarra-Amaya; Andrés Arturo Venegas Segura; Nelson Ricardo Fino-Puerto (Revista Científica General José María Córdova, 2023)
The defense of collective rights and the appropriate reparation of damages to victims is a recent development issue in the Colombian legal system. Although some legal provisions mentioned damages to an indeterminate group of people in cases of negligence, it was not until the 1991 Constitution that Colombia established the types of actions all individuals or groups can initiate to advocate for the integrity of their rights in the face of illegal actions or omissions by the State. There is currently no mechanism for groups to sue private entities efficiently that guarantees all individual and collective rights, akin to class actions. This scientific article delves into the multifaceted landscape of collective rights protection in Colombia, focusing specifically on the mechanisms and implications surrounding the deployment of group actions.